Associations between attention-deficit/hyperactivity disorder symptoms and dietary habits in elementary school children. (1st August 2018) - Kim, Kyoung Min; Lim, Myung Ho; Kwon, Ho-Jang; Yoo, Seung-Jin; Kim, Eun-jung; Kim, Jun Won; Ha, Mina; Paik, Ki Chung
Abstract: Objective: The aim of the present study was to investigate the associations between dietary habits and attention deficit/hyperactivity disorder (ADHD) symptoms in elementary school children. Methods: The parents of 16, 831 participating children assessed the ADHD symptoms of their children by responding to the Korean version of the ADHD rating scale (K-ARS). Parents also responded to the food habit questionnaire, which consists of 8 items regarding the eating pace, the frequency of overeating, and patterns of eating six types of food: fast food, soft drinks, instant noodles, fruit and vegetables, and milk. Results: K-ARS scores were positively associated with higher consumption of foods categorized as unhealthy, including fast food, soft drinks, and instant noodles, and negatively associated with higher consumption of fruit and vegetables categorized as healthy foods. K-ARS scores were also higher in the groups who overate more frequently and ate faster or slower compared to other family members. Conclusion: Our findings may provide useful clinical information for dietary interventions in children with ADHD.